(untitled) (Research, Society and Development, 2021)
To report on the production of digital educational assistance technologies, related to the guidance of health teams on the correct management of diagnostic tests of suspected patients for Covid-19. It is a theoretical-applied research, with a descriptive character, aimed at reconstructing concepts and ideas to improve the theoretical foundations and apply them in the experienced reality, thoroughly describing the impressions and results obtained with the study. It was divided into 3 stages, with a bibliographic survey, construction of educational health technology, to guide the appropriate technique for collecting the exams and, finally, the elaboration of an explanatory video on the subject. Conducted the confrontation of the pandemic caused by the infection of the new Covid-19, aiming, through active technologies in the health area, to contribute with future prevention strategies, based on the knowledge of professionals and all collaborators that work to combat this great health problem. worldwide health. It was noted that health technologies, which can be linked in openly shared social media, are fundamental to access the public of interest, with a view to social isolation.